Impact of Tide of Times Which Effects Berthing Window Delays at Port of Dwikora Pontianak on Ship PT. Tanto Intim Line - Shaula Rizkiyansyah; Datep Purwa Saputra; Erna S Widodo (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
The purpose of the study is to find out how the tide of times impacts Berthing Window delays at Port of Dwikora on PT. TANTO INTIM LINE. The research was conducted at PT. Tanto Intim Line using descriptive qualitative, and descriptive methods. Data was collected through field observations and literature studies. The results showed that the tide of times has been affected by berthing window delays at Port of Dwikora Pontianak. Tide of Times Impacting ships to berth delays and raised some risks faced by the company, such as losing time of berth window, loading cancellation, and also costs that can arise due to container stacking at the Port of Dwikora Pontianak. Due to the high risks faced by the company, there were still a ship that were not ready to berth because of trouble during sailing time and the coordinator’s lack of understanding regarding the impact of tide of times which effects ship delayed to berth at Port of Dwikora Pontianak.